144k views
2 votes
Solve P = 2 (l + w) for w.w =

2 Answers

4 votes

To solve for w, you need to isolate/get the variable "w" by itself in the equation:

P = 2(l + w) Divide 2 on both sides


(P)/(2) =(2(l+w))/(2)


(P)/(2) =l+w Subtract l on both sides to get "w" by itself


(P)/(2) -l=l-l+w


(P)/(2) -l=w

User Condinya
by
4.5k points
5 votes

Answer:

w = (P/2) - l

Explanation:

Given equation,

→ P = 2(l + w)

Now the value of w will be,

→ P = 2(l + w)

→ 2(l + w) = P

→ l + w = P/2

→ [ w = (P/2) - l ]

Hence, value of w is (P/2) - l.

User Fzzle
by
4.7k points